Prices vs. equity in international climate policy: A broad perspective - Lucas Bretschger; Janick Christian Mollet (ETH Zurich, CER-ETH - Center of Economic Research, 2015)
Effective climate policy can be achieved by implementing either a global uniform carbon price or a global cap and trade system. But depending on the allocation of tax revenues and initial pollution per-mits, the instruments have very different wealth implications for the individual countries. The paper highlights the distributional effects of climate policies by calculating and comparing emission budget alloca-tions under three different schemes that are in line with a 2?C warm-ing target. We calculate implicit carbon budgets up to 2050 under a globally uniform CO2 price, a design proposed by Weitzman (2014). We then compare the allocation with the budget derived from equity principles by Bretschger (2013) and with emission budgets under egalitarian emission rights as proposed by BASIC (2011). Our results show that implicit burden sharing across countries varies substantially with the different policy regimes. Wealthy countries with low energy prices tend to obtain the highest emission budget under a price scheme while poor low-emission countries receive the highest budget under egalitar-ian emission rights. The budget positions of India and the US are illustrative for the conflicting country interests.
Keywords: Q58; Q53; 330; Climate change policy; greenhouse gas emissions; uniform carbon tax; equity principles